Practice teaching handbook - Vega, Violeta A. (Mandaluyong City, 2008)
This handbook aims to help prepare the student teacher for a very important phase of his/ her pre- service preparation, Practice teaching. since practice teaching is the heart of the teacher education program, all the knowledge, skills and abilities acquired by the student teacher in the general, professional and methodology courses will be tested and put to practice.
Keywords: student teaching- handbook, manuals, etc; teachers- training of- handbook, manuals, etc; student teachers